The Gambia : Sixth Review Under the Arrangement Under the Extended Credit Facility and Request for Extension and Augmentation of the Arrangement, and Waiver of Nonobservance of Performance Criterion; Staff Report; Staff Supplement; Press Release; Statement by the Alternate Executive Director for The Gambia. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Sixth Review Under the Extended Credit Facility (ECF) for The Gambia. Recent performance under the ECF-supported program continued to be broadly satisfactory. All quantitative performance criteria for end-September 2009 were achieved, except for the fiscal target, and there was good progress on the structural agenda. IMF staff recommends approval of the authorities' request for a waiver for the nonobservance of the fiscal performance criterion based on corrective actions, notably the government budget for 2010 approved by the National Assembly with a near-zero basic balance.